2009
DOI: 10.1080/02642060902749369
|View full text |Cite
|
Sign up to set email alerts
|

The roles of personality and general ethical judgments in intention to not repay credit card expenses

Abstract: There are no 'card slaves' but only cardholders who cannot meet their obligations. Recently, the issue that people are plagued by huge credit card debt has become more serious in Taiwan. This study proposed a model linking personality traits (locus of control (LOC) and risk-taking propensity), general ethical judgments regarding credit card use, and behavioral intention to not repay credit card expenses. External LOC and risk-taking propensity can predict intention to not repay through ethical judgments. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…; McMahon & Harvey ; Ding et al . ; Sparks & Pan ). We therefore applied a hypothetical scenario – known as a vignette – in which a protagonist has committed an ethically questionable act.…”
Section: Introductionmentioning
confidence: 99%
“…; McMahon & Harvey ; Ding et al . ; Sparks & Pan ). We therefore applied a hypothetical scenario – known as a vignette – in which a protagonist has committed an ethically questionable act.…”
Section: Introductionmentioning
confidence: 99%
“…These have included "whistle blowing" where respondents evaluate the appropriateness of a vignette protagonist disclosing others' questionable activities (e.g., Ayers and Kaplan, 2005;Barnett et al, 1994, Vignette 19;Barnett et al, 1996;Chiu, 2003;Chiu and Erdener, 2003;Hansen, 1992, Vignettes 2 and 3;Jung, 2009, Vignette 3;Radtke, 2000;Zhang et al, 2009a,b), laying off an employee (e.g., Cohen et al, 1998, Vignette 5;Shawver and Sennetti, 2009;Valentine and Hollingsworth, 2012), paying for inside information (e.g., Valentine and Rittenburg, 1994), bribery (e.g., , software piracy (e.g., Wagner and Sanders, 2001), and behavior in the face of threats or pressure from superiors or clients (e.g., managers explicitly ordering vignette protagonists to engage in bribery and price-fixing, Smith et al, 2007; see also Barnett et al, 1994, Vignettes 3 and 18;Cohen et al, 1998, Vignette 4;Cruz, Shafer, and Strauser, 2000;Flory et al, 1992;Loo, 2004;Marques and AzevedoPereira, 2009, Vignettes 1 and 5;Patel, 1993, Vignettes 1 and 2;Shawver and Sennetti, 2009). Some vignettes involve activities that create no apparent harms of any kind and thus seem not to be ethically questionable at all, such as consumers bringing their own shopping bags to stores (Chan et al, 2008), customers applying for credit cards but rarely using them (Ding et al, 2009), refunding money to customers (Dornoff and Tankersley, 1975), extending credit or loans that violate only the lenders' "normal (internal) lending criteria" (e.g., Flory et al, 1992;Cohen et al, 1998, Vignette 2;Shawver and Sennetti, 2009), and hiring Hispanic persons for a Mexican restaurant (Schepers, 2003).…”
Section: Ethical Judgments 28mentioning
confidence: 99%
“…Locus of control has emerged as orthogonal to ethical judgments in six vignettes (Razzaque and Hwee, 2002), in two vignettes (Bass et al, 1999), in five of six vignettes relevant to credit card use (Ding, Chang, and Liu, 2009), and in a whistle blowing vignette (Chiu, 2003). Chiu and Erdener (2003), also in the context of whistle blowing, reported that locus of control correlated positively with ethical judgments in the Hong Kong sample, and negatively with behavioral intentions in the Shanghai sample.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…Among the psychological variables that have often been found to be associated with higher debt are more tolerant attitudes towards debt (Lea et al, 1993), a more external locus of control (e.g. Ding, Chang & Liu, 2009;Livingstone & Lunt, 1992;Tokunaga, 1993; though contrast Lea et al1995;Wang, Chen & Wang, 2008; and, for student samples, Norvilitis, Szablicki & Wilson, 2003;Trent, Lee & Owens-Nicholson, 2006), a sense of inadequacy about money or money management (e.g. Lea et al, 1995;Stone & Maury, 2006), and excessive optimism , for the general population; Seaward & Kemp, 2000, for students).…”
Section: Previous Literature: the Antecedents Behaviour And Consequementioning
confidence: 99%